RISET IMPLEMENTASI PENGAJARAN TIGA PILAR GEREJA SUARA KEBENARAN INJIL MELALUI METODE EKSPLANATORI - KONFIRMATORI - Jos Sudarman Lauwanto (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
This research had a purposed was to determine how much the implementation of the teaching of the three pillars of the Bible's Truthful Voice Church (abbreviated as GSKI), then what dimensions are dominant and what background categories are dominant in the teaching of the three pillars. The method that researchers use is a quantitative method with an explanatory-confirmatory approach. The researcher submitted a statement questionnaire to the officials of the Jakarta Gospel Truth's Church. Based on the research results obtained, it turns out that the magnitude of the implementation of the teaching of the three pillars of the GSKI is at a high level, then the dominant dimension is responsibility and the dominant background category is the length of service of church officials. With these results, the recommendation is to maintain a high level by making systematic teaching modules, holding seminars on the three pillars of the GSKI, holding regular meetings between the central board and church officials, and selecting candidates for officials selectively and objectively.